Host lignin composition affects haustorium induction in the parasitic plants Phtheirospermum japonicum and Striga hermonthica. Issue 2 (2nd March 2018) - Cui, Songkui; Wada, Syogo; Tobimatsu, Yuki; Takeda, Yuri; Saucet, Simon B.; Takano, Toshiyuki; Umezawa, Toshiaki; Shirasu, Ken; Yoshida, Satoko
Summary: Parasitic plants in the family Orobanchaceae are destructive weeds of agriculture worldwide. The haustorium, an essential parasitic organ used by these plants to penetrate host tissues, is induced by host‐derived phenolic compounds called haustorium‐inducing factors (HIFs). The origin of HIFs remains unknown, although the structures of lignin monomers resemble that of HIFs. Lignin is a natural phenylpropanoid polymer, commonly found in secondary cell walls of vascular plants. We therefore investigated the possibility that HIFs are derived from host lignin. Various lignin‐related phenolics, quinones and lignin polymers, together with nonhost and host plants that have different lignin compositions, were tested for their haustorium‐inducing activity in two Orobanchaceae species, a facultative parasite, Phtheirospermum japonicum, and an obligate parasite, Striga hermonthica . Lignin‐related compounds induced haustoria in P. japonicum and S. hermonthica with different specificities. High concentrations of lignin polymers induced haustorium formation. Treatment with laccase, a lignin degradation enzyme, promoted haustorium formation at low concentrations. The distinct lignin compositions of the host and nonhost plants affected haustorium induction, correlating with the response of the different parasitic plants to specific types of lignin‐related compounds. Our study provides valuable insights into the important roles of lignin biosynthesis and degradation in the production of HIFs. Abstract : See also the Commentary on this article byRich, 218 : 404–406 .